Improved ion-exchange column chromatography for Cu purification from high-Na matrices and isotopic analysis by MC-ICPMS. Issue 4 (3rd March 2020) - Kidder, James Andrew; Voinot, Alexandre; Sullivan, Kaj Vaughan; Chipley, Donald; Valentino, Marissa; Layton-Matthews, Daniel; Leybourne, Matthew
Abstract : Measurements of Cu isotopes from low concentration and high salinity matrices require high recovery and purity prior to measurement. A new automated two-stage chromatographic procedure yields highly pure Cu separations, low procedure blanks and much-improved reproducibility. Abstract : Measurements of Cu isotopes from low concentration and high salinity matrices require high recovery and purity, prior to measurement. An automated two-stage chromatographic procedure, combining a pre-purification stage to remove the majority of matrix elements (AG® 50W-X12), with an adaptation of an existing method using anion exchange resin AG®MP-1 has been used to overcome these problems. A series of matrices were tested, from low (river water) to high salinity (synthetic seawater, human serum), using several standards and reference materials such as Trace Metals 1 (−0.21‰ ± 0.08 2SD), SLRS-5 (+0.30‰ ± 0.05 2SD), Seronorm™ (−0.25‰ ± 0.04 2SD), and NASS-7 seawater, doped with ERM®-AE633 (0.00‰ ± 0.14 2SD). Results demonstrated highly pure (>98%) Cu separations, low procedure blanks (<1% of loaded Cu), and much improved measurement reproducibility of <0.14‰ (2SD) for high salinity samples. This is an important development for δ 65 Cu measurement from low Cu concentrations commonly encounted in research of medical isotope metallomics, mineral exploration, and environmental geochemistry. As with other studies, combining standard-sample bracketing with Ga for internal normalisation to correct instrumental mass bias (C-SSBIN) resulted in a significant improvement in the precision of measurements ( versus standard sample bracketing alone), typically improving the external reproducibility of measurements from 0.10 down to 0.03‰ (2SD).